Environmental degradation to economic growth and sustainable development in developing countries / Halimahton Borhan - Borhan, Halimahton (2006)
This study attempts to see the relationship between environmental degradation to economic growth in developing countries by taking into account the environmental Kuznets curve. The focus on environmental degradation is on air pollution and developing country is Malaysia. The researcher attempt to measure the actual shape of Environmental Kuznets curve (EKC) in response to modem environment regulation in Malaysia. The EKC relationship has usually been used as a theoretical model to represent the change in pollution levels in a city over time as economic development proceeds. Although this relationship for air pollution is almost impossible to test when the data for air quality at the early stages of industrialization does not exist, however there are some historical accounts of air quality prior to the industrial revolution that can be used. The general objective of the study is to measure the relationship between economic growth and different indicators of air pollution in Malaysia. Air pollution indicators were assessed on a number of measures: Carbon Monoxide (CO), Sulphur Dioxide (S02), Nitrogen Dioxide (N02), Ozone (03) and Particulate Matter (PM10). The income level per capita GDP (Gross Domestic Product) per capita were measured from the year 1996 to 2005. The objective is to test an association between Carbon Monoxide (CO), Sulphur Dioxide (S02), Nitrogen Dioxide (N02), Ozone (03) and Particulate Matter (PM10) with income per capita or in other words to test whether GDP per capita has an impact on Carbon Monoxide (CO), Sulphur Dioxide (S02), Nitrogen Dioxide (N02), Ozone (03) and Suspended Particulate Matter (SPM) and vise versa. In the EKC literature, EKC is always estimated in the form of a single equation. However, since both income and environmental quality are endogenous variables in which they impact upon each other, therefore the estimation of single equation relationships where simultaneity exists will produce biased and consistent estimates. The researcher specify the channels through which the income affects pollution and pollution affects income in a conceptual model and then formulate a two-equation simultaneous model for empirical research. The researcher test for exogeneity with the Hausman test and estimate the simultaneity model using the two-stage least squares method. The cubic N-inverted shaped relationships are found between all indicators of air pollutants and GDP per capita in Malaysia. Air pollution however, does significantly affect income.